25‐hydroxyvitamin D and increased all‐cause mortality in very old women: the Newcastle 85+ study. (20th June 2014) - Granic, A.; Aspray, T.; Hill, T.; Davies, K.; Collerton, J.; Martin‐Ruiz, C.; von Zglinicki, T.; Kirkwood, T. B. L.; Mathers, J. C.; Jagger, C.
Abstract: Objective: To investigate the associations between low and high concentrations of baseline serum 25‐hydroxyvitamin D [25(OH)D] and all‐cause mortality in very old (≥85 years) men and women over 6 years. Design, setting and subjects: Prospective mortality data from 775 participants in the Newcastle 85+ Study were analysed for survival in relation to 25(OH)D (season‐specific quartiles and predefined cut‐off values) and sex using Cox proportional hazards models. The models were fitted to the entire and restricted (nonusers of vitamin D‐containing supplements and medication) cohorts. Results: For the entire cohort, mortality was higher in both the lowest and highest 25(OH)D season‐specific quartiles [SQ1: hazard ratio (HR) 1.31, 95% confidence interval (CI) 1.01–1.69, P = 0.04; SQ4: HR 1.44, 95% CI 1.12–1.85, P = 0.004] compared with the combined middle quartiles (SQ2 + SQ3), after adjustment for sociodemographic factors. The increased risk for the highest quartile remained significant after further adjustment for lifestyle variables (SQ4: HR 1.37, 95% CI 1.06–1.77, P = 0.02) and was seen only in women in sex‐specific analyses. Similarly, in sensitivity analyses with predefined 25(OH)D cut‐off values, the highest 25(OH)D concentration (≥75 nmol L −1 ) was associated with a 2.4‐fold increased risk of mortality in women (restricted cohort) after adjusting for all covariates. Conclusion: Low and high season‐specific 25(OH)D quartiles were associated with increased risks of mortality over 6 years in the very old; this effect was particularly noticeable in women, including those who reported taking vitamin D‐containing supplements/medication.